Paprika on a large scale in Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Mike Randall explains how growing paprika on a large scale does require considerable investment, particularly in chemicals and labour, but offers financial rewards in foreign currency.